2016
DOI: 10.1159/000451059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cognitive Function Change on Mortality in Renal Transplant and End-Stage Renal Disease Patients

Abstract: Background: Limited evidence from small-scale studies, mainly involving end-stage renal disease (ESRD) patients, suggests that kidney transplantation may improve cognitive function. We examined changes in cognitive function after a kidney transplant and its association with survival in advanced chronic kidney disease (CKD)/ESRD patients. Methods: In a prospective study design, cognitive performance of 90 patients (50.6 ± 13.1 years, 66.7% men, 27.8% blacks, 76% CKD stages 4-5) was assessed at the respective pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
(37 reference statements)
0
15
0
3
Order By: Relevance
“…This is largely due to the wide use of the Mini-Mental State Examination (MMSE) in this group (Folstein, Folstein, & McHugh, 1975), which only provides a measure of general cognition. These deficits compound normal cognitive aging (Buchman et al, 2009), are exacerbated with CKD progression (Romijn et al, 2015) and are related to an increased risk for mortality (Sharma et al, 2016) and comorbid conditions such as dementia (Bugnicourt, Godefroy, Chillon, Choukroun, & Massy, 2013;Weng et al, 2012).…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
“…This is largely due to the wide use of the Mini-Mental State Examination (MMSE) in this group (Folstein, Folstein, & McHugh, 1975), which only provides a measure of general cognition. These deficits compound normal cognitive aging (Buchman et al, 2009), are exacerbated with CKD progression (Romijn et al, 2015) and are related to an increased risk for mortality (Sharma et al, 2016) and comorbid conditions such as dementia (Bugnicourt, Godefroy, Chillon, Choukroun, & Massy, 2013;Weng et al, 2012).…”
Section: Cognitive Impairment In Ckdmentioning
confidence: 99%
“…First, intact neurocognition is critical for long-term management of a complex medical regimen. 9 - 11 Second, neurocognitive functioning appears to worsen in the presence of delirium and other untoward neurological events 12 , 13 and has been shown to be predictive of long-term survival. 14 Third, it is possible that the risk of some neurological sequelae, and biobehavioral consequences after transplantation, can be mitigated by greater understanding of the occurrence and etiology of these events.…”
mentioning
confidence: 99%
“…13 Most studies have suggested improvement in cognitive functioning after successful kidney transplantation. 9,11,12,[14][15][16][17][18][19] Comparing the neuropsychological performance of patients before and after showed a significant improvement in memory performance after kidney transplantation, whereas other cognitive domains seemed to be unaffected. 15,16 However, in similar research, renal transplant recipients showed improved attention, memory, executive functioning as well as an improved psychomotor speed after successful kidney transplantation.…”
Section: Introductionmentioning
confidence: 98%